Identifying Indicators of Readiness and Capacity for Implementing Farm‐to‐School Interventions. (1st April 2019) - Lee, Eunlye; Smathers, Carol; Zubieta, Ana C.; Ginnetti, Sarah; Shah, Anjli; Freedman, Darcy A.
ABSTRACT: BACKGROUND: Farm‐to‐school interventions are recommended strategies to improve dietary behaviors among school‐aged children. Tools are needed to assess community readiness and capacity to optimize farm‐to‐school implementation. The objective of this study was to identify and prioritize factors to inform tailored farm‐to‐school implementation by practitioners working in diverse contexts. METHODS: Practitioners and community residents (N = 194) participated in semistructured interviews (N = 18) and focus groups (N = 23). Thematic analysis was conducted to identify themes and subthemes influencing farm‐to‐school implementation. The subthemes were operationalized into measureable indicators. The themes and their associated indicators were prioritized through a consensus conference with an expert panel (N = 18). RESULTS: The qualitative data analysis and consensus conference yielded 4 themes and 17 indicators associated with community readiness and capacity to implement farm‐to‐school. The themes represent school capacity, networks and relationships, organizational and practitioner capacity, and community resources and motivations. CONCLUSIONS: Findings highlight a range of indicators of community readiness and capacity needed to support farm‐to‐school implementation. Results offer guidance for tailoring intervention delivery based on levels of community, school, practitioner, and organizational readiness and capacity.